A novel approach to band gap engineering of Nano-Ca(OH)2: Nanocomposites with Ag2O. Issue 23 (1st December 2022) - Harish,; Kumar, Pushpendra; Kumar, Vipin; Mishra, Rajneesh Kumar; Gwag, Jin Seog; Singh, Manoj K.; Singhal, Rahul; Mukhopadhyay, Anoop Kumar
Abstract: Band gap engineering (BGE) is an important tool to tune the energy band gap of wide band gap semiconductors e.g., Ca(OH)2 which promises to show many wonderful functional applications e.g., solar blind photodetectors. The current work reports about the successful reduction in optical energy band gap (Eg ) through BGE of chemically synthesized Ca(OH)2 nano particles (CHNPs) by microstructural tuning achieved through in-situ Ag2 O incorporation to achieve the formation of the Ca(OH)2 –Ag2 O nanocomposites. The CHNPs and (3–15 atom%) Ag2 O-incorporated CHNPs nanocomposite powders are characterized by the conventional x-ray diffraction (XRD), x-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM), energy dispersive x-ray (EDX) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, thermo-gravimetric analysis-differential thermal analysis (TGA-DTA) and ultraviolet–visible (UV–Vis) UV–Vis spectroscopy techniques. The results reveal that systematic incorporation of nano Ag2 O can very effectively reduce the magnitude of direct optical band gap energy values (Eg ) by as much as 33%. These results are explained in terms of microstructural variables e.g., nanocrystallite size, lattice strain, lattice parameters, dislocation density, presence of Ag 0, Ag + states present on the surfaces of the nanocomposite powders, variation in microstructure, presence of surface functional groups, thermal stability, and optical absorption characteristics. The possible mechanisms active behind the reduction in the (Eg ) values are suggested. Further, a schematic model of the band gap reduction mechanism is presented. Furthermore, the implications of the present results for designing CHNPs for futuristic applications e.g., optoelectronics are also presented. Graphical abstract: Image 1